Phenotypical stability of common bean lines in three growing seasons in São Paulo State, Brazil - Carbonell, Sérgio Augusto Morais; Pompeu, Antônio Sidney (Pesquisa Agropecuaria Brasileira, 2000)
Aiming at knowing the yield potential behavior of selected common bean lines based on data of phenotypical stability, two experimental sets were carried out in the three traditional growing seasons: rainy (September-October), dry (January-February) and winter (May-June). The first set, with 47 trials, was made up of 16 experimental lines and the check Carioca 80SH cultivar; the second, with 44 trials, was made up of 11 lines and the checks Carioca 80SH and Rosinha G2 cultivars, allocated to the three growing seasons above cited. The experimental design was a randomized complete block with five replications and plots constituted of a line of 5 m of length. Joint (general and seasonal) and single (per season) statistical analyses were performed on the yield data. Phenotypical stability and responsiveness were estimated by Cruz et al. (1989). Several adapted lines in unfavorable environments were observed in at least a growing season. Several genotypes showed high responsiveness or stability. The results indicated the feasibility of recommending cultivars through the selection of the best adapted and responsive experimental lines, specific for each growing season.